2018
DOI: 10.4028/www.scientific.net/kem.770.179
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Ti-6Al-4V Alloy Samples Fabricated by Selective Laser Melting

Abstract: Ti-6Al-4V (wt%) alloy samples with dog-bone and box shapes respectively were fabricated by selective laser melting (SLM). The microstructures and mechanical properties of the 3D printed Ti-6Al-4V samples with and without heat treatment were characterized and tested. The microstructures of the as-fabricated dog-bone shaped samples were mainly composed of acicular α’ phase. After annealing at 700°C, the acicular α’ phase changed into an α/β lamellar structure. After solution treatment at 955°C, water quenching a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…13. On the other hand, the content of the α/α' phases affects the corrosion performances [2,5,51,52]. The corrosion resistance of SLM-ed Ti-6Al-4V alloys become better as the volume fraction of α phases increase.…”
Section: Discussionmentioning
confidence: 99%
“…13. On the other hand, the content of the α/α' phases affects the corrosion performances [2,5,51,52]. The corrosion resistance of SLM-ed Ti-6Al-4V alloys become better as the volume fraction of α phases increase.…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, selective laser melting (SLM) process is used for fabrication of the FJP nozzle tool from Titanium alloy Ti6Al4V (also known as Ti64) which possesses good properties such as high strength, corrosion resistant, etc. 23…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, selective laser melting (SLM) process is used for fabrication of the FJP nozzle tool from Titanium alloy Ti6Al4V (also known as Ti64) which possesses good properties such as high strength, corrosion resistant, etc. 23 The present work is an attempt to polish AISI H13 die steel material using FJP process with a custom designed 3D printed Ti6Al4V (Ti64) multi-nozzle tool. The combined effect of spindle rotation and feed rate using 3D printed Ti64 tool in FJP process is very less reported in the available literature.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the addition of GO, the microhardness was significantly increased. The microstructure and mechanical properties of SLM Ti–6Al–4V alloy were studied by Gao et al [ 21 ] The results showed that the microstructure of the specimen was mainly composed of an acicular α′ phase. After heat treatment, the microstructure was composed of a primary α phase and an α/β lamellar structure.…”
Section: Introductionmentioning
confidence: 99%